2014
DOI: 10.1371/journal.pone.0097906
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Functional Chemical-Protein Associations to Identify Multi-Pathway Renoprotectants

Abstract: Typically, most nephropathies can be categorized as complex human diseases in which the cumulative effect of multiple minor genes, combined with environmental and lifestyle factors, determines the disease phenotype. Thus, multi-target drugs would be more likely to facilitate comprehensive renoprotection than single-target agents. In this study, functional chemical-protein association analysis was performed to retrieve multi-target drugs of high pathway wideness from the STITCH 3.1 database. Pathway wideness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Inhibition of HO-1 by the antagonist, ZnPP, increased autophagy in the mesangial cells stimulated with H 2 O 2 . A previous study demonstrated that activation or inactivation of HO-1 does not alter basal autophagy (21). The results of the present study indicated that the effect of HO-1 on reducing autophagy may be ROS-dependent in glomerular mesangial cell.…”
Section: Activation Of Ho-1 Reverses H 2 O 2 -Induced Autophagysupporting
confidence: 51%
See 1 more Smart Citation
“…Inhibition of HO-1 by the antagonist, ZnPP, increased autophagy in the mesangial cells stimulated with H 2 O 2 . A previous study demonstrated that activation or inactivation of HO-1 does not alter basal autophagy (21). The results of the present study indicated that the effect of HO-1 on reducing autophagy may be ROS-dependent in glomerular mesangial cell.…”
Section: Activation Of Ho-1 Reverses H 2 O 2 -Induced Autophagysupporting
confidence: 51%
“…The HO-1-induced effect was also demonstrated to be dose-dependant, as HO-1 successfully inhibited the increasing autophagy caused by H 2 O 2 . However, no significant alteration in the basal autophagy level was detected in normal mesangial cells through the pharmacological intervention of HO-1 activity (21). This implies that the HO-1-mediated control of autophagy may be ROS-dependent.…”
Section: Discussionmentioning
confidence: 88%
“…Hemin induction of HO-1, in the current study, significantly affected oxidative stress conferred by DN, by reversing all oxidative stress markers tested to more favorable antioxidant status. The nephro-protective effect conveyed by induction of HO-1 was linked to its antioxidant effect in previous studies performed in vitro using H 2 O 2 -treated glomerular mesangial cells [43] and in vivo using other animal models, as polymyxin B-induced nephrotoxicity [44] and gentamicin-induced nephrotoxicity [45]. Here, we also showed that HO-1 induction via HM caused significant reversal of increased renal tissue NO levels, which is in line with previous studies linking the induction of renal HO-1 with that of inducible nitric oxide synthase (iNOS) [33].…”
Section: Discussionmentioning
confidence: 93%
“…It was not surprising that miR-133a, a validated biomarker for osteoporosis ( Wang et al, 2012 ; Li et al, 2014 ), targeted genes in six osteoporosis-related pathways. Based on our previous studies of multi-pathway renoprotectants ( Xu et al, 2014 ), enriched regulation of multiple pathways associated with osteoporosis may suggest a potential functional role for miR-194-5p in the pathogenesis of osteoporosis.…”
Section: Discussionmentioning
confidence: 97%